Two Cheers for "Two Concepts": Isaiah Berlin's Skeptical, Tragic Liberalism. Issue 4 (1st October 2020) - Thomas, George
ABSTRACT: Returning to Isaiah Berlin's "Two Concepts of Liberty" offers a defense of liberal democracy that can help us come to terms with its limits, as well as the implicit tradeoffs that are an inescapable feature of politics in a liberal democracy. While critics of Berlin are right to note his neglect of Enlightenment constitutionalism, his skeptical liberalism is illuminated by comparative constitutional law, where we see how different constitutional regimes balance different values—such as democracy, liberty, and equality—in different ways that are attuned to the particulars of place and history that both Berlin and critics of liberalism insist are so important.